Sea motorways as a part of the logistics chain - Paulauskas, Vytautas; Bentzen, Kent (Transport, 2008)
This paper presents the main tools of Sea Motorways as an important part of the logistics chain and can be used presented methodically as a framework for designing logistics or supply chains along with sea motorways. Various factors influencing the choice of logistics chains with sea motorway part are described. The methodology of evaluating sea motorways and the logistics chain is furnished. The paper concludes by identifying the best logistics chains including sea motorways. First published online: 27 Oct 2010